2002
DOI: 10.1186/1471-2474-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine-evoked pain in fibromyalgia. A randomized pilot study ISCRTN70707830

Abstract: Background: Fibromyalgia syndrome displays sympathetically maintained pain features such as frequent post-traumatic onset and stimuli-independent pain accompanied by allodynia and paresthesias. Heart rate variability studies showed that fibromyalgia patients have changes consistent with ongoing sympathetic hyperactivity. Norepinephrine-evoked pain test is used to assess sympathetically maintained pain syndromes. Our objective was to define if fibromyalgia patients have norepinephrine-evoked pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 16 publications
3
42
0
2
Order By: Relevance
“…In apparent contrast to the above, some authors have demonstrated basal LC-NE hyperfunction [111]and increased central CRH release [112]in FM patients. Such discrepant findings might be due to associated anxiety, depression, sleep disturbances, level of physical activity/deconditioning, diet factors such as caffeine consumption, variation of LC-NE/HPA axis functioning over time, and heterogeneity of FM subgroups [48, 113, 114].…”
Section: Possible Pathophysiological Mechanismsmentioning
confidence: 95%
See 1 more Smart Citation
“…In apparent contrast to the above, some authors have demonstrated basal LC-NE hyperfunction [111]and increased central CRH release [112]in FM patients. Such discrepant findings might be due to associated anxiety, depression, sleep disturbances, level of physical activity/deconditioning, diet factors such as caffeine consumption, variation of LC-NE/HPA axis functioning over time, and heterogeneity of FM subgroups [48, 113, 114].…”
Section: Possible Pathophysiological Mechanismsmentioning
confidence: 95%
“…Sympathetic hyperfunction may be related to the clinical observation of a whole range of neurovegetative symptoms in FM and experimental findings of NE-evoked pain in these patients [111]. …”
Section: Possible Pathophysiological Mechanismsmentioning
confidence: 99%
“…Some of these studies showed elevated function in the sympathetic nervous system. [4][5][6][7] Martinez-Lavin et al [19] suggested that fibromyalgia patients have norepinephrine-evoked pain which may be resolved by sympatholytic maneuvers. They also proposed that sympathetic hyperactivity may explain some of the manifestations of FMS including sleep disorders, irritable bowel syndrome, sicca symptoms and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…However, when an acute stress is imposed on the system, notably under conditions in which the monoamine system is challenged, the COMT deficiency can be uncovered in a pattern consistent with gene-environment interaction. This might well be the case in fibromyalgia (Martinez-Lavin & Hermosillo, 2000;Martinez-Lavin et al, 2002).The COMT Val158Met polymorphism has been linked to a decrease in pain tolerance in healthy volunteers (Zubieta et al, 2003). Studies on healthy volunteers have also shown greater brain activation in the limbic region of Met/Met carriers in reaction to an emotionally challenging situation such as the presentation of unpleasant stimuli (Zubieta et al, 2003;Smolka et al, 2005Smolka et al, , 2007Drabant et al, 2006).…”
mentioning
confidence: 99%